Primary and lower secondary students’ learning agency and social support - Soini, Tiina; Pietarinen, Janne; Ulmanen, Sanna; Anttila, Henrika; Pyhältö, Kirsi (Frontline Learning Research, 2023)
Making initiatives and having ownership over one’s learning is a key for applying and creating knowledge, acquiring new abilities, actively steering one’s life and the engaging in change in society. Understanding the preconditions for such learning should be in the core of designing learning environments and the primary interest of frontline learning research. This study focuses on exploring students’ sense of their learning agency in studying and the role of teacher and peer support in cultivating it. We examined how primary (grades 1-6) and lower secondary school students (grades 7-9) perceive their learning agency (LA), its relationship with the experienced teacher and peer support in studying. Also, differences between the girls and boys, and schools located in low and high SES neighborhoods was examined. We assessed the structure and level of learning agency by using a new measurement and explorative structural equation modeling (ESEM). Results show that learning agency consists of interdependent elements of motivation to learn, self-efficacy beliefs about learning and strategies for learning in meaning making, problem solving and scaffolding in studying. The experienced learning agency was related to social support experienced in several ways. Also differences in learning agency and social support in terms of grade level, gender and SES were detected. Results indicate that meaning making especially calls for intentional support from teachers in lower secondary grades and that girls and boys have partly different support needs in terms of cultivating strong sense of learning agency.